Refining a Software System Deployment Process Model: A Case Study - Panizzi, Marisa Daniela (2021)
Software system deployment describes the activities associated with ensuring that a software system is available for its end users. Every company, regardless of its size, requires an efficient and effective software system deployment process to ensure the customer will accept the system software successfully. Small and Medium Enterprises (SMEs) often operate on limited resources and with strict time constraints, and need to improve their processes. For this reason, the existing proposals for deployment processes are not usually useful for SMEs. This fact led us to propose DepProMod (Deployment Process Model) to help SMEs to execute the deployment process of software systems in a systematized and controlled manner. The initial version of DepProMod has subprocesses, activities and tasks defined in addition to a capabilitylevel architecture which allow its implementation in a step-by-step manner. This paper presents the results of a case study we carried out in order to examine the feasibility of the implementation of the initial version of DepProMod in a real environment with the purpose of refining it (if necessary) and completing it. We worked with the deployment process documentation of the “Company creation” module of a management system of advertising agencies for Latin America, in a software development SME in Argentina, to analyze the information requirements of the deployment procesgs and thus move towards the design of templates. In addition, a set of good practice recommendations was designed, not only for the deployment process but also for the rest of the company's software processes.